Analysis of Real Economy Impact on Stock Markets and its Utilization for Investment Activities - Belan, Michal; Stádník, Bohumil; Bayer, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The goal of this thesis is to analyze the reaction of world's most important stock markets and currencies to various macroeconomic news and policies of central banks and to use these researched relationships for setting the most efficient investment and speculation strategy on how to grasp these opportunities, when they repeat in future. The thesis is divided into three chapters. Chapter one focuses on setting of the conceptual and theoretical framework for the thesis, examining the behavior of markets from different perspectives, provided by eminent market participants and most influential theories. Chapter two outlines the strategy for grasping of the short- and long-term trading opportunities, created by market adjustments to different kinds of macroeconomic news. Chapter three backtests, optimizes and evaluates proposed short-term strategy for trading of economic news.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses